1978
DOI: 10.1002/1097-0142(197811)42:5<2206::aid-cncr2820420518>3.0.co;2-s
|View full text |Cite
|
Sign up to set email alerts
|

Adjuvant radiation therapy for regional nodal metastases from malignant melanoma. A randomized, prospective study

Abstract: After nodal metastasis from malignant melanoma, approximately 80% of patients die from disseminated disease. To clarify the role of radiation therapy (XRT) following node dissection. 56 patients with biopsy-proven nodal metastasis participated in a randomized, prospective clinical trial which compares radiation therapy to the regional lymph node area following lymphadenectomy (27 patients) with lymphadenectomy alone (29 patients). Interesting differences in the survival curves (p = 0.09) and in the disease-fre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
38
0
4

Year Published

1990
1990
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 123 publications
(43 citation statements)
references
References 9 publications
1
38
0
4
Order By: Relevance
“…Two randomized controlled trials [338,339] confirmed six retrospective cohort studies [336,337,340,341,343,345] in showing significantly higher locoregional control rates in patients with lymph node metastases undergoing postoperative adjuvant radiation therapy of the affected lymph node basins. In Burmeister et al, 34 of 127 patients without radiation therapy sustained locoregional lymph node recurrence, whereas in the patient group subjected to adjuvant radiation therapy, 20 patients suffered recurrence within the lymph node basin.…”
Section: Level Of Evidence 2bmentioning
confidence: 78%
See 2 more Smart Citations
“…Two randomized controlled trials [338,339] confirmed six retrospective cohort studies [336,337,340,341,343,345] in showing significantly higher locoregional control rates in patients with lymph node metastases undergoing postoperative adjuvant radiation therapy of the affected lymph node basins. In Burmeister et al, 34 of 127 patients without radiation therapy sustained locoregional lymph node recurrence, whereas in the patient group subjected to adjuvant radiation therapy, 20 patients suffered recurrence within the lymph node basin.…”
Section: Level Of Evidence 2bmentioning
confidence: 78%
“…Systematic search of the literature de-novo: [336][337][338][339][340][341][342][343][344][345] Strength of consensus: 100%…”
Section: Level Of Evidence 2bmentioning
confidence: 99%
See 1 more Smart Citation
“…Since such relapse is very difficult for treatment, there were attempts to obtain better results with postoperative radiotherapy. Although some phase II studies showed certain efficacy ), the only randomized study did not show any difference, neither in DFS, nor in OS (Creagan et al, 1978). Radiotherapy in metastatic melanoma is especially significant for symptoms palliation, primarely of pain due to bone metastases ).…”
Section: Radiotherapymentioning
confidence: 96%
“…Sinusal melanoma irradiation was proved useful and it is safe for the fetus. Adjuvant irradiation after lymphadenectomy proved no benefit in a randomized study (Creagan et al, 1978), so it should be avoided in pregnancy. A specific question is when to irradiate a pregnant patient with metastatic melanoma.…”
Section: Radiotherapy Of Melanoma In Pregnancymentioning
confidence: 98%